Digital Transformation in Human Resource Management: Enhancing Financial and Non-Financial Rewards in Nepalese Commercial Banks (Victoria Journal of Management, 2025)
This study explores the impact of digital transformation on Human Resource Management practices in Nepalese commercial banks, with a focus on enhancing financial and non-financial rewards for employees. The study examines how the adoption of digital tools, such as Human Resource Management Systems, Business Intelligence and Data Analytics tools, Customer Relationship Management systems, Cybersecurity tools, and Blockchain and Fintech innovations influence reward systems within the banking sector. Financial rewards, including salary and bonuses, as well as non-financial rewards such as recognition, work-life balance, and career development, are considered as dependent variables, while the independent variables are the various digital tools and systems utilized by the banks. Data were collected through structured questionnaires distributed to employees across 20 commercial banks in Nepal. The analysis of the data, using correlation coefficients and regression models, reveals a significant positive relationship between the implementation of digital tools and the enhancement of both financial and non-financial rewards. The study indicates that the effective use of HRMS, business intelligence, and CRM systems improves transparency and fairness in the distribution of financial rewards. Additionally, digital tools contribute to better employee engagement and satisfaction through the personalization of nonfinancial rewards. The findings suggest that digital transformation plays a crucial role in improving HR practices, fostering a more motivated and committed workforce, and increasing overall employee performance and retention in Nepalese commercial banks.